Copyright life hacks for librarians - Claire Sewell; John Clarke; Amy Theobald (Insights: The UKSG Journal, 2020)
Librarians are continuously looking for new ways to make the training they offer accessible and engaging to both colleagues and users. One area where this is especially important is copyright – a topic many librarians identify as vital to their role, but they often find it hard to attend training. Cambridge University Libraries has introduced a range of methods to reach out to even the most reluctant copyright learner and improve the overall copyright literacy of its staff. This article showcases these methods in the form of ‘life hacks’ – simple measures which can be implemented with little or no cost and using existing resources. Methods outlined include making the best use of knowledge already present within your organisation, using visual methods to attract a new audience and creating interactive online resources. Also discussed is the importance of making copyright training accessible, both to users with disabilities and those who may have constraints on their time and technological ability. The article concludes with a reflection about the challenges faced whilst creating new resources. The techniques outlined in this case study can be adapted for use by a range of libraries no matter the target audience.